Urogenital abnormalities in men exposed to diethylstilbestrol in utero: a cohort study - Palmer Julie R; Herbst Arthur L; Noller Kenneth L; Boggs Deborah A; Troisi Rebecca; Titus-Ernstoff Linda; Hatch Elizabeth E; Wise Lauren A; Strohsnitter William C; Hoover Robert N (BMC, 2009)
Abstract Background Diethylstilbestrol (DES), a synthetic estrogen widely prescribed to pregnant women during the 1940s70s, has been shown to cause reproductive problems in the daughters. Studies of prenatally-exposed males have yielded conflicting results. Methods In data from a collaborative follow-up of three U.S. cohorts of DES-exposed sons, we examined the relation of prenatal DES exposure to occurrence of male urogenital abnormalities. Exposure status was determined through review of prenatal records. Mailed questionnaires (1994, 1997, 2001) asked about specified abnormalities of the urogenital tract. Risk ratios (RR) were estimated by Cox regression with constant time at risk and control for year of birth. Results Prenatal DES exposure was not associated with varicocele, structural abnormalities of the penis, urethral stenosis, benign prostatic hypertrophy, or inflammation/infection of the prostate, urethra, or epididymus. However, RRs were 1.9 (95% confidence interval 1.13.4) for cryptorchidism, 2.5 (1.54.3) for epididymal cyst, and 2.4 (1.54.4) for testicular inflammation/infection. Stronger associations were observed for DES exposure that began before the 11th week of pregnancy: RRs were 2.9 (1.65.2) for cryptorchidism, 3.5 (2.06.0) for epididymal cyst, and 3.0 (1.75.4) for inflammation/infection of testes. Conclusion These results indicate that prenatal exposure to DES increases risk of male urogenital abnormalities and that the association is strongest for exposure that occurs early in gestation. The findings support the hypothesis that endocrine disrupting chemicals may be a cause of the increased prevalence of cryptorchidism that has been seen in recent years.